PENGUATAN MODAL SOSIAL BAGI UMKM SUKU ANAK RAWA KAMPUNG PENYENGAT KECAMATAN SUNGAI APIT KABUPATEN SIAK - Rd. Siti Sofro Sidiq; Indrawati Indrawati; T. Romi Marnelly; Mita Rosaliza; Muhammad Ihsan; Mochammad Lathif Amin; Seger Sugiyanto (LPPM Universitas Abdurrab, 2025)
Strengthening social capital is key in improving the economic and social welfare of communities, especially for marginalized groups, such as MSMEs among indigenous peoples. This service aims to strengthen social capital for MSMEs of the Anak Rawa Tribe in Penyengat Village, Sungai Apit District, Siak Regency, with a focus on increasing the capacity of social networks, trust between members, and access to resources that support the sustainability of their business. The number of participants in the service was 20 people consisting of representatives of the village government, traditional leaders, women leaders, business actors, and community leaders. The approach used in the service is Participatory Rural Appraisal, an approach that directly involves community members in the process of problem identification, activity implementation to evaluation. In terms of measuring the success of activities, the direct impact of changes in behavior, perspective, and other positive things cannot be seen. However, the service team distributed questionnaires to the participants to review their opinions on the material provided. First, regarding the principle of benefits. Based on the data collected, it can be concluded that all respondents said the material was useful for them. Second, related to the clarity of material delivery. It can be concluded that the delivery of the service material was very clear. Third, regarding how important social capital is for the sustainability of MSMEs. It can be concluded that the service participants consider that social capital is important for the sustainability of MSMEs. Finally, about the elements that are most beneficial for MSME business development. A total of 9 service participants answered that social networks were important, the rest were trust and norms. With the service activities, participants became more aware of the benefits of social capital for business sustainability in terms of trust, norms to networks.